PENGARUH KUALITAS PELAYANAN TELLER TERHADAP LOYALITAS NASABAH TABUNGAN IB HASANAH DI BNI SYARIAH KANTOR KAS JATINANGOR - Sari, Anisa Wulan; Nur’aeni, Nur’aeni (Jurnal Maps (Manajemen Perbankan Syariah), 2018)
The purpose of this research is to know whether there is influence of teller service quality on customer loyalty of iB hasanah savings in BNI Syariah Jatinangor Cash Office. The research used descriptive method with quantitative approach. The main source of research is questionnaires distributed to 46 respondents. Data is processed with the help of IBM SPSS Statistic 23.The result of research shows that the correlation level of influence of teller service quality on customer loyalty of iB hasanah saving account is 0,326 and is in low category. The result of the calculation of Test Z, known that Zhitung> Ztabel or 2.184> 1.64. This means that H0 is rejected and H1 is accepted, meaning there is influence between teller service quality to customer loyalty saving iB hasanah in BNI Syariah Jatinangor Cash Office. The coefficient of determination obtained is 0.106 or 10.6%, it means that in general the quality of service contributes influence of 10.6% to customer loyalty. While the rest as much as 89.4% influenced by other factors such as promotion mix, price and so forth.This research reveals that customers expect not to wait long to get teller service so it is suggested if under certain conditions (crowded atmosphere) teller more than one person. There is further research to know other factors that influence customer loyalty besides quality of service of teller like promotion mix, price and others in order to know other factor which more influence customer loyalty.